A Retrospective Study to Determine the Type of Offence Committed by the Juveniles in the Reformatory Schools of a Capital City of India (Medico Legal Update, 2020)
Background: Juveniles of today will become the adults of tomorrow, the face of the world. Hence, it is ofutmost importance to make sure that the youth of nation are given a wholesome protected environment tothrive and grow in. Aim of the Study: Our study was focussed on retrospectively studying the type of offencecommitted by the juveniles in the reformatory schools. Material & Method Both male and female inmatesof the reformatory schools were studied for the unlawful acts which landed them into the Reformatoryschools. Observation & Results: The percentage of boys and girls involved in non-heinous and otheroffences was 36.5% and 33.3% respectively; but this association of type of offence with gender was foundto be statistically non-significant (p>0.05).There were 103 cases of sexual offences, maximum Cases wereof POCSO. Conclusion: Comprehensive violence prevention plans in all spheres of life, i.e. homes, schools,communities to reduce and prevent juvenile delinquency. Special programmes should be designed to preventsexual reoffending among these juveniles. Development of facilities for counselling and psychological andpsychiatric treatment as well as introduction of Juvenile mentoring programs is highly recommended inreformatory schools.